Barriers to Success in Parent Training for Young Children With Developmental Delay: The Role of Cumulative Risk. (May 2013) - Bagner, Daniel M.; Graziano, Paulo A.
The purpose of this study was to examine the effect of cumulative risk on dropout and treatment outcome in parent training. Participants were 44 families of young children (mean age of 49.59 months) who presented with elevated externalizing behavior problems and developmental delay or borderline developmental delay. All families were offered to receive Parent–Child Interaction Therapy (PCIT), an evidence-based, behavioral parent-training intervention, at a hospital-based outpatient clinic. Cumulative risk was calculated as a sum of risk variables, including socioeconomic disadvantage (poverty, low maternal education), family structure (single-parent household), and maternal risk characteristics (minority status, lower intelligence, and parental distress). Families with higher cumulative risk scores, especially those with three or more risks, were more likely to drop out of treatment and display diminished treatment response in child behavior and parenting skills compared with families with lower cumulative risk scores. However, only two individual risk factors (i.e., minority status and family structure) predicted dropout, and one individual risk factor (i.e., maternal education) predicted outcome. These findings suggest that it can be useful to conceptualize risk factors as having a cumulative, in addition to individual, influence on parent-training interventions for children with developmental delay and have significant implications for clinical practice. It is important for clinicians to regularly assess for risk factors, and future research should examine ways in which clinicians can improve retention and outcome of parent training in the presence of multiple risk factors.